1991
DOI: 10.1111/j.1528-1157.1991.tb05531.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Methylguanidine and Guanidinoacetic Acid in the Brain of Amygdala‐Kindled Rats

Abstract: Guanidino compounds are intrinsic chemoconvulsants. We investigated the regional and time-dependent changes of these compounds in the amygdala (AM) of kindled rats versus electroconvulsive shock (ECS) seizures using high-performance liquid chromatography (HPLC). Twenty-eight days after the last AM-kindled seizure, guanidinoacetic acid (GAA) and methylguanidine (MG) levels were significantly increased in the bilateral AM as compared with those of control rats, which had been implanted with electrodes but were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…We also observed a two-to three-fold increase in GAA and MG levels in the cerebral cortex and hippocampus (2) months after ferric chloride injection into the sentory motor cortex, inducing an epileptic focus (14). Furthermore, GAA and MG levels in bilateral amygdala were shown to increase significantly in the amygdalaor hippocampal-kindled rat (15,16), an experimental model of epilepsy (17).…”
Section: Biochemistryond Molecular Biology Internationalmentioning
confidence: 65%
See 1 more Smart Citation
“…We also observed a two-to three-fold increase in GAA and MG levels in the cerebral cortex and hippocampus (2) months after ferric chloride injection into the sentory motor cortex, inducing an epileptic focus (14). Furthermore, GAA and MG levels in bilateral amygdala were shown to increase significantly in the amygdalaor hippocampal-kindled rat (15,16), an experimental model of epilepsy (17).…”
Section: Biochemistryond Molecular Biology Internationalmentioning
confidence: 65%
“…Previously we observed that levels of GAA and MG markedly increase in the epileptogenic focus of the brain (5,14,15,16) and furthermore we have found that high brain levels of guanidino compounds are potent endogeneous convulsants when administrated by intracisternal injection (4, …”
Section: Discussionmentioning
confidence: 99%
“…The level of MG extremely increases under the pathophysiological condition such as convulsion or chronic renal failure. For example, the levels of MG increased in the epileptogenic focus of the rat brain as experimental animals for epilepsy, i.e., the level of MG in amygdala showed significant increase in the epileptic animal models; amygdala-kindled rats [11,12]. The level of MG in the plasma increased several-fold under the uremic condition [3] when compared to the control.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, it was found that ascorbate, GSH, EPC-K 1 , and Trolox, which are closely linked to redox-system in biological system, effectively inhibited •OH generation from MG, indicating the potential for the protection against the extremely high level of MG and also the prevention of MG formation [11,12,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation